Pengaruh Pembelajaran Proyek Berorientasi Recycled Crafts Terhadap Divergent Thinking Anak Usia 5-6 Tahun di TK Roudhatul Ulum Jember - Anggi Puji Lestari (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to determine the effect of project-based learning using recycled crafts on the divergent thinking skills of early childhood children, focusing on fluency, flexibility, originality, and elaboration. The study employed a pre experimental one-group pretest-posttest design with a quantitative approach. Data collection techniques used were observation, assisted by a Likert-type assessment instrument, with each assessment indicating a different level of development, ranging from underdeveloped to highly developed. The results showed an increase in children's divergent thinking after being treated with the project-based learning model using recycled crafts. The average pretest score was 16.9, increasing to 19.9 in the posttest. Hypothesis testing yielded a significance value of 0.002 <0.05. Based on these results, it can be concluded that the implementation of project-based learning using recycled crafts has a positive effect on the divergent thinking of 5-6 year-old children at Roudhatul Ulum Kindergarten in Jember.
Validasi dan Finalisasi Repositori File 25 Juni 2026_Kholif Basri
Keywords: project-based learning oriented of recycled crafts; divergent thinking 5-6 years old